2007
DOI: 10.1039/b705550a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, NMR conformational analysis and pharmacological evaluation of 7,7a,13,14-tetrahydro-6H-cyclobuta[b]pyrimido[1,2-a:3,4-a′]diindole analogues as melatonin receptor ligands

Abstract: A structure for the self-condensation product of 2-(1H-indol-2-yl)ethyl tosylate 2a, previously proposed as 6,7,14,15-tetrahydro-15aH-azocino[1,2-a:6,5-b]diindole 3a, was revised based on the (13)C-2D-INADEQUATE experiment, and proved to be 7,7a,13,14-tetrahydro-6H-cyclobuta[b]pyrimido[1,2-a:3,4-a']diindole 4a. A mechanism for the unexpected formation of this novel hexacyclic heterocycle was proposed and its NMR solution structure was elucidated. Five derivatives of the title ring skeleton 12-16 designed as me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…Almost all the scaffolds shown in Figure 2 were bearing at least one of these features, with rare exceptions. The ethylamide moiety was either included in a cycle, 33,43,87,94,106,118,122 or bearing a double bond 87,94 or various substituents, such as CF 3 , 45,109,110,120 CHF 2 , 45,132 CH 2 Cl, 34,117 a cyclopropyl moiety 29,102,114,116,133 or a cyclobutyl moiety 42,66 to name only a few.…”
Section: The Alkoxy and N‐acylamino Decorationsmentioning
confidence: 99%
“…Almost all the scaffolds shown in Figure 2 were bearing at least one of these features, with rare exceptions. The ethylamide moiety was either included in a cycle, 33,43,87,94,106,118,122 or bearing a double bond 87,94 or various substituents, such as CF 3 , 45,109,110,120 CHF 2 , 45,132 CH 2 Cl, 34,117 a cyclopropyl moiety 29,102,114,116,133 or a cyclobutyl moiety 42,66 to name only a few.…”
Section: The Alkoxy and N‐acylamino Decorationsmentioning
confidence: 99%
“…More recently, several benzimidazole containing indole and tetrahydronaphthalene indole derivatives were reported as strong inhibitors of lipid peroxidation and superoxide anion formation 16,17 . Several antioxidant pyrimidodiindole and pyridoindole derivatives were studied as melatonin receptor antagonists 18,19 . Recent data from our laboratory showed important antioxidant effects of N-substituted amide [20][21][22][23][24] and ester 25 derivatives of indole.…”
Section: Research Articlementioning
confidence: 99%
“…Furthermore, Moody et al reported that reductive cyclisation of the ethyl 4-(2-nitropheny)-acetoacetate using titanium(III) chloride in aqueous acetone gave 2-(1H-indol-2-yl) acetate with a 75% yield [22]. Despite producing good yields, these methods suffer from indispensable multi-step pre-transformations of commercially available starting materials, and are therefore of limited synthetic scope [23]. Wilkens et al described a one-pot reaction of N-phenylhydroxylamine, benzaldehyde and ethyl 2,3-butadienoate followed by hydrolysismediated production of 2-(1H-indol-2-yl)acetate [24].…”
Section: Introductionmentioning
confidence: 99%